Dynamic Modeling of Market Value and Capital Structure in Nigerian Firms - Ogbonna, Udochukwu Godfrey; Ejem, Chukwu Agwu (International Journal of Economics and Financial Issues, 2019)
In this paper, the researchers employed Panel generalised method moments to examine the controversy facing the dynamic relationship between market value of firms and capital structure. The made use of twenty four quoted firms from ten sectors in Nigeria between 2010 and 2017 inclusive. Modigliani and Miller (1958), states that the value of a firm should not depend on its capital structure whereas Myers (1984) Static Trade-off Theory and Income theory support the relevance of capital structure in determining the firm’s value. However, this study revealed that both equity and debt capital instruments at first difference impact positively and significantly on the market value of firms. That means the researchers findings support the argument that capital structure is relevant to market value of firms. It is the opinion of the researchers that based on the outcome of this study, that firms should have a mix of both debt and equity in their financing structure in order to enhance the market value of the firm. It should be done in an optimal way so as to achieve the desired objective of increase in market value of the firm. Keywords: Market Value, Equity and Debt Capital, Dynamic Modelling, Panel Generalised Method of Moments JEL Classifications: G32, C58 DOI: https://doi.org/10.32479/ijefi.8848